2019
DOI: 10.1186/s12864-019-5622-4
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics identifies patterns of genetic diversity and selection in chicken

Abstract: Background There are hundreds of phenotypically distinguishable domestic chicken breeds or lines with highly specialized traits worldwide, which provide a unique opportunity to illustrate how selection shapes patterns of genetic variation. There are many local chicken breeds in China. Results Here, we provide a population genome landscape of genetic variations in 86 domestic chickens representing 10 phenotypically diverse breeds. Genome-wide analysis indicated that sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 65 publications
3
36
1
1
Order By: Relevance
“…They possess their own genetic structure in subgroups. In admixture result, game breeds and red jungle clustered as one group until K = 16, suggesting domestic breeds and wild populations have mutual introgression (Li et al, 2019;Wang et al, 2020). It is consistent with our NJ tree results that all breeds from the same population clustered, except that game breeds.…”
Section: Discussion Population Structure and Genetic Diversitysupporting
confidence: 88%
See 1 more Smart Citation
“…They possess their own genetic structure in subgroups. In admixture result, game breeds and red jungle clustered as one group until K = 16, suggesting domestic breeds and wild populations have mutual introgression (Li et al, 2019;Wang et al, 2020). It is consistent with our NJ tree results that all breeds from the same population clustered, except that game breeds.…”
Section: Discussion Population Structure and Genetic Diversitysupporting
confidence: 88%
“…On chromosome 11, more than 33% of the Silkies chickens, 24% of the Tibet chickens and 14% of Hongshan chickens had a ROH in the region from 1.91 to 4.00 Mb, from 2.31 to 5.66 Mb, and from 2.30 to 3.91 Mb, which contained NECAB2, SLC38A8, and NFATC3 genes, and several potential candidate genes for silky feathers. On chromosome 3, we showed that up to 40% of Beijing You chickens had a ROH between 69.38 and 70.93 Mb, retaining the gene ASCC3 which is also a candidate gene for silky feathers (Li et al, 2019). Besides, on chromosome 2, chromosome 3, and chromosome 13, we identified several potential candidate genes associated with egg production, eggshell quality and growth traits, such as GDF9, OPN, CDH9, CDH10, and KIF18A (Pines et al, 1995;Hincke et al, 2010;An et al, 2012;Lin et al, 2014;Wang et al, 2020).…”
Section: Genomic Inbreeding and Runs Of Homozygosity Islandmentioning
confidence: 89%
“…Genes for aesthetic physical phenotypes including height, stature, coat and plumage colour are commonly encountered in genomic regions under selection in domestic animal populations since they are easily identifiable [42][43][44][45] . Conformation characteristics are among the most discernible traits in horses and are the principal observable traits on which Thoroughbreds are selected.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Due to its economic and agricultural importance, the wild progenitor of the Domestic Chicken, Gallus gallus (Red Junglefowl), was the first avian species whose genome was completely sequenced (ICGSC 2004). Since then, genomes of many of the hundreds of different breeds of Gallus gallus have been sequenced (e.g., Imsland et al 2012;Yi et al 2014;Wang et al 2015;Lawal et al 2018;Li et al 2019;Yang et al 2019), resulting in a large number of available chicken genomes.…”
Section: Introductionmentioning
confidence: 99%